Amduat-Exemplare von Thutmosis I.: Weitere Fundstücke im Grab KV 38 - Ghany, Khaled Abdel (Zeitschrift für ägyptische Sprache und Altertumskunde, 2019)
This article deals with the further exploration in tomb KV 38 in the Valley of Kings. In the course of this exploration in early 2018 I discovered more small mud-plaster fragments of the Amduat book. These different Amduat fragments can be identified as a part of the fourth, sixth, seventh, eighth and tenth hour of the book of Amduat. Therefore, these Amduat fragments prove that possibly the cliff walls of the tomb of king Thutmose I were originally encased and decorated with a complete corpus of the book of Amduat (long version). After an examination of the displayed scenes and their comparison with similar sections of the Amduat from tomb KV 34 it turned out that both specimens show clear differences and that both tombs have manifold artistic variations. Therefore, both specimen are originate from different reigns and were not made by the same king.